THE INTERCHANGE OF LANGUAGE AND PHILOSOPHY IN SUNDANESE SPEECH LEVEL SYSTEMS - Jaelani, Alan; Nuruddin (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
Sundanese speech level system i.e., kasar (coarse), loma (moderate), and lemes (polite) represents a culturally significant yet underexplored area in linguistic and philosophical research. Despite its role in reflecting Sundanese values such as unggah-ungguh (harmonious relationships), existing studies have largely focused on descriptive aspects and overlooked its deeper cultural and philosophical implications. This study aimed to investigate how Sundanese speech levels capture social hierarchies, interpersonal relationships, and cultural philosophies. Employing a qualitative methodology, this study involved literature reviews, textual analyses, and comparative evaluations of universal linguistic theories against Sundanese-specific findings. The results indicate that kasar is used in informal settings to reflect equality or emotional expressiveness; loma maintains a neutral politeness appropriate for everyday interactions; and lemes conveys deference and respect in hierarchical or formal contexts. These levels align with Sundanese cultural philosophies emphasizing respect, harmony, and social order. Universal linguistic theories of speech act provided a foundational lens but required adaptation to account for cultural specificity. Sundanese speech level system is not merely a linguistic structure but a philosophical expression of cultural values. It demonstrates how language reflects and reinforces social and ethical norms, contributing to a deeper understanding of the interplay between language, culture, and philosophy